Anti-Occlusion Algorithm for Object Tracking Based On Multi-Feature Fusion - Jie Cao; Liang Xuan (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Complex background, especially when the object is similar to the background in color or the target get blocked, can easily lead to tracking failure. Therefore, a fusion algorithm based on features confidence and similarity was proposed, it can adaptively adjust fusion strategy when occlusion occurs. And this confidence is used among occlusion detection, to overcome the problem of inaccurate occlusion determination when blocked by analogue. The experimental results show that the proposed algorithm is more robust in the case of the cover，but also has good performance under other complex scenes.